A Mini Review on Working Mechanism, Standard Operating Procedure (SOP) and Preventative Maintenance of Low Temperature Long Term (LTLT) Milk Pasteurizer - A., Asogan; N., Sazali; F. M., Said; R. Z., Edros; M. F., Ghazali; S. A., Che Ghani (Penerbit UMP, 2023)
A small-scaled batch Low Temperature- Long Term (LTLT) pasteurizer is one of many types of pasteurizers that is being utilized in food-based industries particularly in dairies. It has a capacity of heating up the milk and holding the temperature for a certain amount of time to kill pathogenic microorganisms. The instantaneous heat up is caused by heat exchangers either in the form of plates or metal coils depending on the machine. The coil is circulated within the jacket of the tank where it heats up and holds the temperature. Hot water circulation will be in continuous movement around the milk to heat it up and maintain the desired temperature. After certain period, the efficiency of LTLT pasteurizer starts declining due to cumulated issues. Decline in efficiency will affect the output of the machine too. Instantaneous heat exchanges, leaking, unstable pressure and electrical problem degrades the machine over period if it is not complying with Standard Operating Procedure (SOP) and a proper Preventative Maintenance (PM) plan. The SOP and PM will increase the machine’s lifespan and maintain a good efficiency rate for longer period. This mini review paper will compile the possible PM plan and establish a sustainable SOP for the LTLT Pasteurizer.